The Effect of Workload, Work Motivation and Work Environment on Employee Job Satisfaction - Tania Laurencia Mandjar; Joyce A. Turangan (International Journal of Application on Economics and Business, 2023)
Employee job satisfaction is the individual's level of satisfaction for a role or job in an organization. Researchers have pointed out that employees with higher satisfaction tend to be more loyal and productive. This study aimed to analyze the effects of workload, work motivation, and work environment on employee job satisfaction. The research sample was 110 employees of PT. Andalan Ekspor Indonesia using the non-probability sampling technique. The research method uses SmartPLS and data for conducting this research was obtained through filling out questionnaires through Google Form. The results showed that there is a negative influence of workload on the job satisfaction of employees of PT. Andalan Ekspor Indonesia and a positive influence of work motivation and work environment on the job satisfaction of employees of PT. Andalan Ekspor Indonesia.